HBOC-201 Vasoactivity in a Phase III Clinical Trial in Orthopedic Surgery Subjects-Extrapolation of Potential Risk for Acute Trauma Trials. - Freilich D; Pearce LB; Pitman A; Greenburg G; Berzins M; Bebris L; Ahlers S; McCarron R (Journal of Trauma, 2009)
BACKGROUND:: Vasoactivity has hampered progress of hemoglobin-based oxygen carriers (HBOCs) due to concern for adverse blood pressure responses and secondary complications. A recent formulation, highly polymerized HBOC-201 (Biopure, Cambridge, MA), has been found to be less vasoactive than prior less polymerized formulations, and to improve outcome in animal models of hemorrhagic shock (HS) compared with standard resuscitation fluids. HBOCs are envisioned to have life- saving potential for severe trauma patients for whom death due to HS is common despite transport to level I trauma centers. As part of a benefit:risk analysis for a proposed clinical trial of HBOC-201 in patients with traumatic HS, we analyzed data from a previous phase III clinical trial of this HBOC that involved orthopedic surgery patients, for vasoactivity and related effects, with focus on patients more representative of the trauma population. STUDY DESIGN:: In a previous phase III study involving orthopedic surgery patients, HEM-0115, consented/stabilized patients were randomized to receive HBOC-201 (N = 350) (up to ten 30 g Hb units) or red blood cells (RBC) (N = 338) (up to 9 units) at the first transfusion decision. Systolic blood pressure (SBP) responses, key system and individual adverse events (AEs) and serious adverse events, and cardiac biomarker elevation incidences, were compared in the overall population and subpopulations with stable trauma, hypotension, and with age stratification (Student's t and Fisher's exact tests, significance p < 0.05). RESULTS:: Mild to moderate peak SBP responses were common in HBOC-201 subjects and more common than with RBC in the overall population (mean, 60.8 years old), but less frequent in HBOC-201 subjects with stable trauma, younger age (<50 years old), and hypotension, in whom group differences were narrowed. SBP Delta responses were more common with HBOC-201 than RBC in the overall population, but not in subjects with stable trauma and <50 year olds, in whom response rates were lower. In the overall population, AEs were more common than with RBC in most systems (also, hypertension and stroke); only cardiac system serious adverse events were more common with HBOC-201. In contrast, there were few significant group differences in stable trauma, hypotensive, and <70 and especially <50-year-old subjects, in whom AE incidences were generally lower. A disproportionate number of key AEs occurred in elderly subjects. Troponin (but not CK-MB) elevation was more frequent with HBOC-201 than RBC in the overall population but not in <50 year olds, and was not associated with acute coronary syndrome (ACS) or death. CONCLUSIONS:: Our limited HEM-0115 safety analysis shows that key potentially vasoactivity-related adverse safety signals were more frequent with HBOC-201 than RBC in older patients undergoing orthopedic surgery with rapid access to safe blood transfusions. That incidences of these safety signals were generally lower and group differences narrowed in subpopulations with stable trauma, hypotension, and younger age, suggests an acceptable safety profile in younger acute trauma populations, especially in settings where rapid access to safe blood transfusions is unavailable; confirmation in controlled clinical trials is urgently warranted.